The Paths to Realizing Reconciliation: Indigenous Consultation in Jasper National Park - Johnston, Jason W.; Mason, Courtney W. (The International Indigenous Policy Journal, 2020)
Diverse Indigenous nations have traditional territories inside Jasper National Park (JNP), but the park was established without consultation with local Indigenous communities. Parks were marketed as empty landscapes, which celebrated romantic ideas of European colonial expansion. The current representations of Indigenous Peoples in interpretive content still reflect this lack of consultation. This research was guided by Indigenous methodologies. Data was collected through interviews with Jasper Indigenous Forum (JIF) members and the JNP management team. Findings indicate that JIF members want increased representation and greater control over how their histories and cultures are presented. Park management needs to work in close consultation with the JIF if they want to improve Indigenous representations in the park and support processes of reconciliation.